Socio-cultural conditions of the Internet network becoming - Dabrarodni, Danila G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is dealed the problem of comprehension the phenomenon of the Internet by philosophy and other sciences. The article describes the Internet becoming since the first computer network ARPANET has appeared until its mass distribution and use. The author has revealed a unique combination of socio-cultural conditions and factors that enabled the first appearing of this technology and then to gain universal acceptance. These are political (the situation of the Cold War, democratic institutions), economic (the emergence of a global market economy, a new generation of entrepreneurs), technical and technological (microprocessor revolution), axiological (the values of scientific creativity and freedom of communication)factors. The author defined the most important characteristics of the Internet, which determined his popularity among users, and their connection with changes in society and culture in general.
Keywords: philosophy of technology; philosophy of Internet; Internet evolution; socio-cultural conditions and factors of the Internet becoming; Internet culture